2021
DOI: 10.17826/cumj.920570
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting obesity in preadolescents: the case of Cappadocia

Abstract: This cross-sectional study was conducted to determine the risk factors which affect obesity in preadolescents. Materials and Methods:The sample of the study consisted of 500 preadolescents (girls: n=271, boys: n=229) attended in 18 secondary schools in the Cappadocia region of Turkey, and their parents. Data were collected using a questionnaire, the body weight, height, and waist circumference of the preadolescents were measured; the body mass index (BMI) and the waist-toheight ratio were calculated. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Regarding anthropometric measurements, to the best of our knowledge, there is no study investigating the relationship between nutrition literacy with waist, hip and neck circumference among adolescents. Although nutritional literacy was associated with healthy lifestyle behaviours, the non-significant association between nutrition literacy and BMI and anthropometric measurements can be explained by the fact that these parameters are influenced not only by the nutritional literacy level but also by other factors such as lifestyle, environmental, psychological and genetic factors ( 44 ) . The present study did not examine the relationship between these other factors and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding anthropometric measurements, to the best of our knowledge, there is no study investigating the relationship between nutrition literacy with waist, hip and neck circumference among adolescents. Although nutritional literacy was associated with healthy lifestyle behaviours, the non-significant association between nutrition literacy and BMI and anthropometric measurements can be explained by the fact that these parameters are influenced not only by the nutritional literacy level but also by other factors such as lifestyle, environmental, psychological and genetic factors ( 44 ) . The present study did not examine the relationship between these other factors and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several cross sectional and longitudinal studies endorsed this statement, reporting evidence of the association between mood dysregulation and medical conditions, such as obesity or hypertension, in children and adolescents. A study conducted in Turkey, the European country with the highest rates of overweight and obesity, found increased eating behaviours associated with negative feelings in preadolescents, possibly as a coping strategy, that can result in weight gain ( 125 , 126 ). Regarding the direct relationship of mood disorders with obesity and hypertension in children and adolescents, Medrano et al reported results about cardiovascular risk factors in youth with overweight and obesity ( 127 ).…”
Section: Family and Social Relationsmentioning
confidence: 99%